2021
DOI: 10.1177/03009858211009785
|View full text |Cite
|
Sign up to set email alerts
|

Value, Limitations, and Recommendations for Grading of Canine Cutaneous Mast Cell Tumors: A Consensus of the Oncology-Pathology Working Group

Abstract: One of the primary objectives of the Oncology Pathology Working Group (OPWG), a joint initiative of the Veterinary Cancer Society and the American College of Veterinary Pathologists, is for oncologists and pathologists to collaboratively generate consensus documents to standardize aspects and provide guidelines for oncologic pathology. Consensus is established through review of relevant peer-reviewed literature relative to a subgroup’s particular focus. In this article, the authors provide a critical review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 24 publications
0
47
1
1
Order By: Relevance
“…This consensus guideline proposes the use of both the classification systems suggested by Patnaik et al [ 48 ] and by Kiupel et al [ 80 ], for a better classification of the disease (e.g., “MCT grade 3 according to Patnaik and high-grade according to Kiupel”). The recommendation is in line with the recommendation of the American College of Veterinary Pathologists and the Veterinary Cancer Society [ 54 ].…”
Section: Diagnostic Approachmentioning
confidence: 64%
See 2 more Smart Citations
“…This consensus guideline proposes the use of both the classification systems suggested by Patnaik et al [ 48 ] and by Kiupel et al [ 80 ], for a better classification of the disease (e.g., “MCT grade 3 according to Patnaik and high-grade according to Kiupel”). The recommendation is in line with the recommendation of the American College of Veterinary Pathologists and the Veterinary Cancer Society [ 54 ].…”
Section: Diagnostic Approachmentioning
confidence: 64%
“…They concluded that all techniques were adequate in differentiating between low-grade and high-grade MCTs. Some grade 2/high-grade cases may be underestimated in pre-operative biopsies, and are, thus, not recommended as the only source of therapeutic guidance and tumor staging [ 54 ].…”
Section: Diagnostic Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Mast cell tumors (MCTs) are the most common and frequently diagnosed malignant skin tumors in dogs, accounting for 7 to 21% of all skin neoplasms [ 1 , 2 , 3 ]. The clinical presentation, gross appearance, and biological behavior of canine cutaneous MCTs varies widely [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mast cell tumors (MCTs) are the most common skin tumor affecting dogs, and the tumor grade is the most consistent and clinically relevant prognostic factor [1][2][3][4]. There are two MCT grading systems: the Patnaik system and the Kiupel system [3].…”
Section: Introductionmentioning
confidence: 99%